العلل الخفية في كتاب "الغرائب والأفراد" للدارقطني بترتيب ابن طـــــــاهر المقـــــــــدسي (من بداية مسند أبي هريرة رضي الله تعالى عنه إلى نهاية مسند ضباعة رضي الله تعالى عنها) (نماذج من دراسة نقدية تحليلية للأحاديث المعلولة): The Hidden Defects in al-Dāraqutnī’s “al-Gharāʾib wa al-Afrād” (as arranged by Ibn Ṭāhir al-Maqdisī): A Critical Analytical Study of Ḥadīths from the Musnad of Abū Hurayrah to the Musnad of Ḍubāʿah (may Allah be pleased with them) (Al-Aasar, 2025)
This paper investigates a selected section of Imām al-Dāraqutnī’s Kitāb al-Gharāʾib wa al-Afrād, arranged by Ibn Ṭāhir al-Maqdisī, focusing on narrations from the Musnad of Abū Hurayrah to the Musnad of Ḍubāʿah (may Allah be pleased with them). The study aims to identify and analyze hidden defects (ʿilal khafiyyah) within these narrations using an inductive and analytical approach. By comparing transmission routes, evaluating narrators, and identifying points of variation, the research uncovers the critical methods employed by al-Dāraqutnī in detecting subtle errors in isnād and matn. Major findings reveal that most narrations exhibit defects due to tafarrud, disconnection, or contradiction between rafʿ and waqf. The study concludes that al-Dāraqutnī’s methodology reflects exceptional precision in hadith criticism and underscores the continuing relevance of ʿIlal al-Ḥadīth in safeguarding the authenticity of the Prophetic Sunnah